Effects of Salidroside Combined with Paclitaxel on Proliferation, Migration, and Epithelial Mesenchyme of Colorectal Cancer Cells - Hao Y; Li Z; Chang M; Zhang X (Dove Medical Press, 2022)
Yanjiao Hao, Zhiyu Li, Mingzhi Chang, Xiaoli Zhang Department of Life Science Research Center, College of Basic Medicine, Hebei North University, Zhangjiakou, Hebei, 075000, People's Republic of ChinaCorrespondence: Xiaoli Zhang, Department of Life Science Research Center, College of Basic Medicine, Hebei North University, Zhangjiakou, Hebei, 075000, People's Republic of China, Tel +8618931316301, Email 894915208@qq.comBackground: Colorectal cancer (CRC) is a multifactorial disease and one of the most common malignancies worldwide. Salidroside (Sal) is a plant with a wide range of pharmacological effects and plays an important role in the treatment of many diseases, and is considered a new hope for the treatment of tumors. The purpose of this study was to investigate the effect of the combination of Sal and paclitaxel (Pac) on colorectal cancer cells and its mechanism of action.Methods: The effects of different mass concentrations of Sal, Pac, and the combination intervened in the cells for 48 h were examined using the CCK8 method. The inhibition rate was obtained, and the optimal concentration of the respective drug group was screened. The proliferative capacity of the respective group was obtained. Subsequently, the results of apoptosis, cloning, migration, invasion, and angiogenesis were observed through cell morphological analysis (shape observation and Hoechst staining), colony formation assay, cell scratching assay, Transwell, angiogenesis assay, and protein immunoblotting (Western blotting) to detect the expression of epithelial-mesenchymal transition (EMT)-associated proteins and PI3K pathway-associated proteins.Results: Different concentrations of Sal, Pac, and the combined application had significant effects in inhibiting cells in a concentration-dependent manner. Compared with the control group, the Sal group, the Pac group, and the combination group significantly inhibited the clonal number, migration, invasion, and tube-forming ability of colorectal cancer cells. Besides, the combined application had a better effect than the Sal and Pac groups. The apoptosis level was up-regulated in all drug groups, and the up-regulation was more significant in the combination group. The expression of E-cad protein was up-regulated, the expression of N-cad and Vim protein was down-regulated, and the expression of PI3K and AKT phosphorylation was down-regulated in the respective group, and the difference was more significant in the combination group compared with the group of individual drugs.Conclusion: The combined application of Sal and Pac significantly can decrease the survival rate of colorectal cancer cells, and the mechanism may be correlated with the blocking of the PI3K/AKT pathway, thus inhibiting EMT.Keywords: salidroside, paclitaxel, colorectal cancer, apoptosis, PI3K/AKT signaling pathway, EMT